(untitled) (Journal of Oriental Studies, 2024)
This article discusses the problem of reviving the spiritual values of the Turkic people. The authors present a theoretical and methodological foundations of development of spiritual values, simulated practical aspects of its implementation. The article shows the main targets of the strategy of Turkish identity in the context of globalization and the inclusion of Kazakhstan in the vectors of development of world culture. In the context of globalization and the formation of a single global information space, the transition to market relations, the situation in the new state the role and importance of Turkish integration increases since understanding that all Turkic peoples have a common history, language and traditions makes the idea of Turkic relevant and meaningful interaction. In today’s geopolitical and inter-civilization integration more actualized the problem of innovation, borrowed and adapted to the socio-cultural and ideological representations arising in the ancient environment that contribute to the consolidation of the Turkic peoples and values of the Turkic world in the context of globalization.